Novizie ed educande nei monasteri italiana post-tridentini - Gabriella Zarri (Universidade do Porto, 2011)
In this study, the Author draws attention to the longevity of female conventual education and analyzes its development, especially from the fifteenth and sixteenth centuries onward, with the diffusion of the novitiate in female religious houses. The Author also studies the cases of the female monasteries in Bologna, in the sixteenth and seventeenth centuries, the range of subjects taught there as well as the two most important works published in the context of the post-Tridentine normative dispositions on nuns and novices: the Specchio religioso per le monache (1609), written by Giovan Pietro Barco, and La monaca perfetta, ritratta dalla Scrittura Sacra con autorità et essempii de’ Santi Padri (1624), by Carlo Andrea Basso.